THE ROLE OF DIGITAL TRANSFORMATION IN ACHIEVING INSTITUTIONAL EXCELLENCE IN NATIONAL SPORTS FEDERATIONS IN IRAQ - Dr. Bahaa Hayder Flayyih (Scholars Digest Publishing, 2025)
Finding out how digital transformation contributes to national sports federations' institutional excellence is the goal of the study. Using correlational connections and the survey technique, the researchers employed a descriptive approach. Using the thorough enumeration approach, the study sample comprised 347 members of Iraq's national sports federations, representing 100% of the research community.. The survey sample, the preparation sample, and the application sample were divided. Scientific foundations were used in preparing the study scales (digital transformation and institutional excellence). The researchers concluded that federations that rely on digital transformation become more able to compete with other federations by providing innovative and value-added services and products. Digital transformation technologies enable sports federations to better understand customer needs through big data analysis. Digital transformation makes national sports federations more flexible in the face of rapid changes in performance and technology. The researchers recommended paying attention to the technology infrastructure in all aspects of digital transformation. National sports federations must pay more attention to an objective system for measuring and evaluating employee performance and strengthening the organizational structure of national sports federations so that it supports effective communication between different departments.
Keywords: Digital transformation, institutional excellence, national sports federations.